Situation Report: Hungary, 12 February 1975 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Preparations for the 11th Party Congress Enter Last Phase (Part One) Trade Unions to Organize Co-operative Workers The Tourist Industry: Problems of Expansion Soviet-Hungarian Goods Exchange Agreement for 1975 Beat under Attack as a Toll of Western Infiltration